Evaluation of Legal Frameworks for Extremism Prevention in Indonesian Higher Education - Agustin, Bunga Veronika Milania; Istiqomah, Milda; Jameelah, Mariyam (Kosmik Hukum, 2026)
Extremism poses a serious challenge to Indonesia’s diversity and national stability, including within higher education institutions. This study aims to evaluate the legal framework governing the prevention of extremism in universities and examine its implementation at Brawijaya University as a case study. Using a socio-legal research method with a digital ethnography approach, the study draws on both primary and secondary data sources. Findings indicate that although several laws and regulations—such as the National Education System Law, the Higher Education Law, and the Presidential Regulation on the National Action Plan for Preventing Violent Extremism—have been established, they remain general and lack specific provisions addressing extremism prevention in higher education. Brawijaya University demonstrates a strong commitment through the issuance of rector regulations, integration of Pancasila values into the curriculum, implementation of nationalism-based student orientation (PKKMB), and partnerships with external bodies such as the Densus 88 counterterrorism unit. However, the absence of a dedicated institutional body to address extremism prevention represents a significant gap that hinders effective implementation. Therefore, the establishment of a specialized unit within each university is urgently needed to strengthen preventive efforts and ensure a safer academic environment.